2007
DOI: 10.1177/0148607107031004302
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ethanol Lock Therapy to Reduce the Incidence of Catheter‐Related Bloodstream Infections in Home Parenteral Nutrition Patients

Abstract: ELT shows promise in reducing the incidence of CRBSI in the frequently infected HPN population. Further studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 20 publications
1
99
1
Order By: Relevance
“…In a small series, adults on home PN were treated with 70 % ethanol for 2-4 h anywhere from 2 to 7 days per week. This treatment resulted in a significant decrease in CRBSI from 8.3 to 2.7 per 1,000 catheter days (Opilla et al 2007). Similarly, a randomized trial in adult oncology patients found that 70 % ethanol used for 2 h daily decreased the infection rate from 3.1 to 0.6 per 1,000 catheter days.…”
Section: Clinical Utility Of Ethanol Locksmentioning
confidence: 84%
See 2 more Smart Citations
“…In a small series, adults on home PN were treated with 70 % ethanol for 2-4 h anywhere from 2 to 7 days per week. This treatment resulted in a significant decrease in CRBSI from 8.3 to 2.7 per 1,000 catheter days (Opilla et al 2007). Similarly, a randomized trial in adult oncology patients found that 70 % ethanol used for 2 h daily decreased the infection rate from 3.1 to 0.6 per 1,000 catheter days.…”
Section: Clinical Utility Of Ethanol Locksmentioning
confidence: 84%
“…Ethanol lock therapy (ELT) is currently used in certain patient populations for both the prevention and treatment of CRBSI (Broom et al 2008;Dannenberg et al 2003;Metcalf et al 2004;Mouw et al 2008;O'Grady et al 2002;Onland et al 2006;Opilla et al 2007). Similar to other lock solutions, the technique involves instilling ethanol within the CVC lumen and allowing it to dwell for a period of time while the catheter is not in use.…”
Section: Clinical Utility Of Ethanol Locksmentioning
confidence: 99%
See 1 more Smart Citation
“…Trials in the adult population have included patients with long-term central venous catheters, such as dialysis, oncology, and PN patients, and have shown variable results. [5][6][7][8] The goal of this study was to further evaluate benefits of adding prophylactic ELT to all patients with silicone-based tunneled catheters in adult patients on home PN for an advanced form of intestinal failure (type 2 or type 3) as defined by the European Society for Clinical Nutrition and Metabolism (ESPEN). 9 The primary outcomes evaluated were the rates of CLABSI and resulting hospitalizations in patients before and after the initiation of the ELT protocol.…”
Section: Role Of Ethanol Locks In Reducing Bloodstream Infections In mentioning
confidence: 99%
“…Taurolidine (a derivative of aminosulfonamide-taurinamide with antimicrobial activity against a broad range of bacteria and fungi), minocycline-EDTA (EDTA is a potent calcium and iron chelateur and has antistaphylococccal and anticandidal activity), gentamycine-citrate solution, ethanol and hydrochloric acid are currently under evaluation [33]. Among them, ethanol appears promising and a double-blind randomized trial to evaluate the efficacy of a 50% ethanol-lock solution instilled for 1-3 h once daily is ongoing [34,35]. Tetrasodium-EDTA, has been tested in vitro and ex vivo with explanted infected hemodialysis catheters [36].…”
Section: Antibiotic-lock Therapymentioning
confidence: 99%